Rapid health evaluation in migrant peoples in transit through Darien, Panama: protocol for a multimethod qualitative and quantitative study. (December 2021) - Gabster, Amanda; Jhangimal, Monica; Erausquin, Jennifer Toller; Suárez, José Antonio; Pinzón-Espinosa, Justo; Baird, Madeline; Katz, Jennifer; Beltran-Henríquez, Davis; Cabezas-Talavero, Gonzalo; Henao-Martínez, Andrés F.; Franco-Paredes, Carlos; Agudelo-Higuita, Nelson I.; et al.
Background: The world is currently unprepared to deal with the drastic increase in global migration. There is an urgent need to develop programs to protect the well-being and health of migrant peoples. Increased population movement is already evident throughout the Americas as exemplified by the rising number of migrant peoples who pass through the Darien neotropical moist broadleaf forest along the border region between Panama and Colombia. The transit of migrant peoples through this area has an increase in the last years. In 2021, an average of 9400 people entered the region per month compared with 2000–3500 people monthly in 2019. Along this trail, there is no access to health care, food provision, potable water, or housing. To date, much of what is known about health needs and barriers to health care within this population is based on journalistic reports and anecdotes. There is a need for a comprehensive approach to assess the health care needs of migrant peoples in transit. This study aims to describe demographic characteristics, mental and physical health status and needs, and experiences of host communities, and to identify opportunities to improve health care provision to migrant peoples in transit in Panama. Study design and methods: This multimethod study will include qualitative ( n = 70) and quantitative ( n = 520) components. The qualitative component includes interviews with migrant peoples in transit, national and international nongovernmental organizations and agencies based in Panama. The quantitative component is a rapid epidemiological study which includes a questionnaire and four clinical screenings: mental health, sexual and reproductive health, general and tropical medicine, and nutrition. Conclusion: This study will contribute to a better understanding of the health status and needs of migrant peoples in transit through the region. Findings will be used to allocate resources and provide targeted health care interventions for migrant peoples in transit through Darien, Panama.